Occurrence of poly-winged fruits on cultivated sycamore maples - Acer pseudoplatanus L - Ivetić Vladan; Tucović Aleksandar (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu, 2003)
The occurrence of polycarpous fruits on six out of 100 sycamore maples, i e. with 3, 4 and 8 fruits on one carpophore is described. Eight-carpous fruits have not been recorded to date in the region of the Serbia and Montenegro, and wider. The cause of the development of polycarpous fruits has been hypothesized.